How factors that potentially influence perceived self-efficacy affect the dietary habits of single, low-income African American mothers - Brown, Nozella Lee (Kansas State University, 2014)
Nutrition educators traditionally rely on quantitative research to design interventions for Supplemental Nutrition Assistance Program (SNAP) audiences, such a low-income African American mothers. Such studies indicated the dietary behaviors of this population related to increased risk for chronic disease. Few studies explored the factors that potentially influenced the perceived self-efficacy and affected the dietary habits of SNAP learners. This study addressed the gap between quantitative research findings about the dietary habits of low-income African American mothers and their perceptions of factors influencing those behaviors. A qualitative bounded multi-site case study design was used to explore factors theoretically linked to social cognitive theory (SCT) that affected the dietary habits of low-income African American mothers. The theoretical framework rested on the interaction between SCT and critical race theory (CRT). The research sample included fifteen women, five from each of three public housing sites. The research design included semi-structured interviews supported by multiple data sources. A pilot study took place. Constant comparison was the technique used to analyze the semi-structured interviews and code the findings. The emergent themes aligned with the theoretical framework to answer the research questions. Triangulation helped to ensure the study’s quality. The findings supported the SCT premise that behavioral, personal, and environmental factors interacted reciprocally to influence dietary habits. The findings supported the CRT tenets that race, history, narratives, and interest convergence mattered and influenced dietary habits. The results had implications for adult educators designing effective nutrition programs for diverse learners.
Keywords: Nutrition education; Social cognitive theory; Critical race theory; Dietary habits; African American women; SNAP-Ed; Adult Education (0516)